Skin rules : trade secrets from a top New York dermatologist - Jaliman, Debra (St. Martin's Press, 2012)
Skin Rules is a concise and practical instruction manual from a renowned Fifth Avenue dermatologist on how to attain beautiful skin, a taut and sculpted body, and a much younger appearance.